Uma educação ambiental da juventude? Avaliação da política pública: Vamos Cuidar do Brasil com as Escolas - Conferências Infanto Juvenis pelo Meio Ambiente no Ceará - Cruz, Lindalva Costa da (2012)
In this study we evaluated the effects of a programme launched in 2004 by the Brazilian Ministry of Education and the Ministry of the Environment entitled “Vamos Cuidar do Brasil com as Escolas”. The purpose of this Programme is to encourage educational experiences that will help prepare for a qualitative leap in the creation of principles directed at preserving the environment. The programme proposes to construct a permanent environmental education process in public schools through a range of actions, with emphasis on the organization of Conferences on Environmental Education for Children and Youths. The third edition of this conference, held in Ceará in 2008, along with the delegates representing Ceará during the regional, national and international stages, is the main object of the study. We investigated how the students have assimilated skills and experiences in environmental education and increased their representativeness in their respective schools and communities. Their observed involvement in environmental education activities reflected the importance of the Programme to their learning process. Our approach was qualitative in order to relate events to human processes, highlighting potential interactions. With the help of questionnaires, in-depth interviews, focus group discussions and free observations, information was collected and entered in a field diary. The results were analyzed using collective subject discourse in order to evaluate the representativeness of the children and adolescents in their respective schools and communities. Our study revealed changes in the studentsʼ attitudes towards their daily routine and their interaction with others and the environment as a result of their participation in the Programme.